2006
DOI: 10.1097/01.qai.0000188336.94090.14
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokines Induce Neutrophils to Chemotaxis, Degranulation, and α-Defensin Release

Abstract: We have previously shown that a Taiwanese cohort of HIV-uninfected individuals was associated with the significantly elevated levels of serum beta-chemokines, macrophage inflammatory protein (MIP-1)-alpha and MIP-beta, and RANTES. In the present study, we report that the members of this cohort have significantly greater numbers of lower buoyant-density neutrophils in their blood, which leads to further investigation of the effects of beta-chemokines on neutrophils. By electron and confocal microscopic techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 37 publications
(55 reference statements)
1
32
0
Order By: Relevance
“…Interestingly, a recent work suggests that ␣-defensins can trigger the release of LTB 4 from alveolar macrophages (19), indicating that ␣-defensins and LTB 4 , through positive feedback loops, can influence each other's formation and release. Even more recently, CC chemokines (RANTES, MIP-1␣, and MIP-1␤) were reported to induce PMN degranulation and ␣-defensin release (39). Considering that LTB 4 also induces the release of human MIP-1␤ under in vivo conditions (29) and that ␤-chemokines trigger the release of ␣-defensins, additive and possibly synergistic effects between LTB 4 and CC-chemokines on ␣-defensin release are expected.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent work suggests that ␣-defensins can trigger the release of LTB 4 from alveolar macrophages (19), indicating that ␣-defensins and LTB 4 , through positive feedback loops, can influence each other's formation and release. Even more recently, CC chemokines (RANTES, MIP-1␣, and MIP-1␤) were reported to induce PMN degranulation and ␣-defensin release (39). Considering that LTB 4 also induces the release of human MIP-1␤ under in vivo conditions (29) and that ␤-chemokines trigger the release of ␣-defensins, additive and possibly synergistic effects between LTB 4 and CC-chemokines on ␣-defensin release are expected.…”
Section: Discussionmentioning
confidence: 99%
“…45 Neutrophils release massive quantities of ␣-defensins upon degranulation in response to cytokines or, as recently reported, CC chemokines. 46 Recent studies have reported elevated levels of CC chemokines in the genital tracts of women who are exposed to HIV-1 and yet remain uninfected. 47 Furthermore, ␣-defensins may play an important role as natural antagonists of HIV-1 entry at the intestinal mucosal level.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes leukocyte recruitment and activation (41). RANTES activates human neutrophil to release antimicrobial peptide ␣-defensins and promote neutrophil phagocytic capacity (42). These effects likely contribute to its host defense against P. aeruginosa infection.…”
Section: Figurementioning
confidence: 99%